Pre‐travel Consultation: Evaluation of Primary Care Physician Practice in the Franche‐Comté Region. Issue 4 (22nd May 2013) - Piotte, Emeline; Bellanger, Anne‐Pauline; Piton, Gaël; Millon, Laurence; Marguet, Philippe
Abstract : Background: Primary care physicians (PCP) are first in line to provide adequate pre‐travel medical advice. Little data are available on the content of pre‐travel PCP consultations in France. We undertook an observational survey to assess the level of specific knowledge among PCPs on health advice, vaccinations, and malaria prophylaxis. Methods: Standardized questionnaires were sent to a random sample of 400 PCPs practicing in the Franche‐Comté regions (eastern France) who were asked to complete and return it on a voluntary and anonymous basis. The questionnaire requested sociodemographic details, practice‐related characteristics, and proposed three clinical situations with multiple choice questions (MCQ). To identify factors associated with a higher level of specific knowledge in travel medicine, results were studied by uni‐ and multivariate analyses. An overall score was calculated based on the MCQ answers and a motivation score was calculated based on parameters such as frequency and developments in pre‐travel consulting at the practice, PCPs' personal experience as travelers, and the formal agreement of PCPs to administer yellow fever vaccination. Results: The response rate was 37.5%, with 150 questionnaires returned completed and suitable for analysis. After multivariate logistic regression, the three variables associated with a higher score were: proximity of a vaccination center ( p  = 0.001), motivation score ( p  = 0.004), and absence of request for expert advice on malaria prophylaxis ( p  = 0.007). Conclusions: PCPs play an important role in travel medicine. This study showed that their high level of knowledge in travel medicine was mostly linked to their motivation to practice in this specialized discipline.